Effect of an Integrated Active Lessons Programme through Playful Maths Games on Self-Concept, Self-Esteem and Social Skills in Preschool Children - Alba Cámara-Martínez; Alberto Ruiz-Ariza; Sara Suárez-Manzano; Rosa M. Cruz-Cantero; Emilio J. Martínez-López (Behavioral Sciences, 2023)
The aim of this study was to analyse the effects of an integrated active lessons programme based on playful math games, of 10 weeks’ duration (30 min/day × 2 days/week), on self-concept, self-esteem and social skills in preschool children. One hundred and ninety-four preschool children (53.6% girls) aged 53.36 ± 11.82 months were split into a control group (CG) and an experimental group (EG). The EG improved significantly in self-concept compared to the CG in boys and girls (6.8% and 7.1%, respectively). Personal and academic self-esteem levels increased significantly (8.1% and 5.5%, respectively, only in girls). Although the EG obtained significant improvements in social self-esteem and social skills compared to the beginning of the study, these results were not found in comparison with the CG. The introduction of active lessons based on playful maths games within the classroom is recommended as support for the improvement in self-concept, self-esteem and social skills in early childhood education.